근시 환자에서 노안교정 비구면 미세단안시 라식 수술의 장기적인 임상 결과 - 강경민; Kyoung Min Kang; 정보영; Bo Young Jung; 조희태; Hee Tae Cho; 이준훈; Jun Hun Lee; 김홍균; Hong Kyun Kim (Daihan angwa haghoi jabji, 2013)
목적: 근시 환자에서 노안교정 비구면 미세단안시 라식 수술의 효능과 안정성 및 환자의 만족도를 알아보고자 한다. 대상과 방법: 2010년 12월부터 2011년 12월까지 노안으로 비구면 미세단안시 라식 수술을 받았던 환자 중 근시환자 18명 36안을 대상으로 하였다. 원거리, 중간거리와 근거리 시력, 구면렌즈대응치 및 환자 만족도를 후향적으로 조사하였다. 결과: 수술 12개월 후 우세안과 양안의 원거리 및 중간거리 나안시력은 모든 환자에서 0.8 이상이었다. 근거리 나안시력은 비우세안의 경우 83%에서 0.5 (J3) 이상이었고 양안의 경우 94%에서 0.5 (J3) 이상이었다. 수술 후 우세안의 평균 구면렌즈대응치는 수술 1, 6, 12개월에 각각 -0.09 ± 0.35D, -0.17 ± 0.42D, -0.17 ± 0.47D였으며 비우세안에서는 각각 -0.94 ± 0.53D, -1.03 ± 0.56D, -1.02 ± 0.50D로 유의한 변화 없이 유지되었다. 수술 후 전반적인 환자의 만족도는 좋았다(5점 만점에 4.2점). 결론: 노안교정 비구면 미세단안시 라식 수술은 모든 거리에서의 나안시력을 호전시키고 굴절부등에 대한 환자의 관용도가 높으며 수술 후 퇴행이 거의 없는 안전하고 효과적인 수술방법으로 생각된다. <대한안과학회지 2013;54(12):1893-1901> Purpose: To evaluate the efficacy, safety, and satisfaction of patients who underwent LASIK for presbyopia correction in myopic patients using aspheric micro-monovision. Methods: LASIK for presbyopic correction using aspheric micro-monovision was performed in 18 patients between December 2010 and December 2011. Distance, intermediate, and near visual acuity, refractive change, and patient`s satisfaction were evaluated for at least 12 months after the surgery. Results: Among dominant eyes, 100% achieved uncorrected distance and intermediate visual acuity of 0.8 or better and 100% of the eyes achieved 0.8 or better binocularly. In the non-dominant eyes, 83% achieved uncorrected near visual acuity of J3 or better, and 94% of the eyes achieved J3 or better binocularly. Postoperatively, the mean manifest refraction spherical equivalent (MRSE) of the dominant eyes were -0.09 ± 0.35D, -0.17 ± 0.42D, and -0.17 ± 0.47D at 1, 6 and 12 months, respectively. The MRSE of the non-dominant eyes were -0.94 ± 0.53D, -1.03 ± 0.56D, and -1.02 ± 0.50D at postoperative 1, 6, and 12 months, respectively, without significant regression. After surgery, the patient`s overall satisfaction score was good (4.2 out of 5). Conclusions: The aspheric micro-monovision protocol showed good distance, intermediate, and near visual outcomes, and was a well-tolerated, stable, and effective procedure for treating patients with myopic presbyopia. J Korean Ophthalmol Soc 2013;54(12):1893-1901